2022
DOI: 10.1155/2022/5080190
|View full text |Cite
|
Sign up to set email alerts
|

Association of Probiotics with Atopic Dermatitis among Infant: A Meta-analysis of Randomized Controlled Trials

Abstract: Background. Previous studies have explored the relationship between probiotics and risk of atopic dermatitis among infant; however, the results are still inconclusive. We aimed to assess the abovementioned association. Methods. PubMed, Web of Science, Embase, and China National Knowledge Infrastructure were retrieved for association between probiotics and atopic dermatitis with randomized controlled trials (RCTs) until Nov 20, 2021. The effect size was pooled by using random or fixed effect models according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Sun et al conducted a meta-analysis of 17 RCTs involving a total of 4,011 children and found that probiotic intervention had a significant benefit in preventing eczema in children [RR (95% CI) =0.59 (0.45, 0.78)] ( 57 ). Pan et al conducted a meta-analysis of eight RCTs involving a total of 2,575 newborns and found that probiotics can effectively prevent AD [RR (95% CI) =0.86 (0.78, 0.95)] ( 58 ). Probiotics can stimulate intestinal immunoglobulin A (IgA), reduce the adhesion of pathogenic bacteria, and form tight junctions with intestinal epithelial cells to decrease intestinal permeability ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al conducted a meta-analysis of 17 RCTs involving a total of 4,011 children and found that probiotic intervention had a significant benefit in preventing eczema in children [RR (95% CI) =0.59 (0.45, 0.78)] ( 57 ). Pan et al conducted a meta-analysis of eight RCTs involving a total of 2,575 newborns and found that probiotics can effectively prevent AD [RR (95% CI) =0.86 (0.78, 0.95)] ( 58 ). Probiotics can stimulate intestinal immunoglobulin A (IgA), reduce the adhesion of pathogenic bacteria, and form tight junctions with intestinal epithelial cells to decrease intestinal permeability ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, study results are inconsistent and mixed, with some groups reporting the positive beneficial effect of probiotics in alleviating AD symptoms and mitigating the risk of AD, but others reporting no effect [ 44 , 45 ]. Despite the ongoing debate on the best practices of probiotic use in treating AD, a number of recent meta-analyses have pooled several clinical trials [ 46 , 47 , 48 , 49 , 50 , 51 ] and shown that certain probiotic strains [ 52 , 53 , 54 ], such as Lactobacillus rhamnosus and Bifidobacterium lactis , may be effective in reducing AD symptoms in children. In addition, mixed probiotic strains with a longer treatment duration have apparently demonstrated better effects in children aged > 1 year [ 46 ].…”
Section: Introductionmentioning
confidence: 99%